Effects of nalbuphine on the cardioprotective effect of morphine in rats. (1st January 2021) - Wu, Lining; Yu, Junma; Wang, Qiuyue; Lu, Yao
Abstract: Background: When combined with morphine, nalbuphine not only does not affect the analgesic effect but also prevents opioid-induced side effects. The authors investigated whether nalbuphine interferes with morphine-induced cardioprotection in rats. Methods: Anesthetized male Sprague-Dawley rats were randomly assigned to 1 of 4 treatment groups. Nalbuphine (NAL, 1 mg/kg) and morphine (MOR, 0.3 mg/kg) were administered 10 and 5 min prior to myocardial ischemia, respectively. Additionally, the NAL + MOR group received the combination of NAL and MOR prior to myocardial ischemia. An in vivo animal model was established by occluding the left anterior descending artery for 30 min and reperfusing it for 2 h. After 2 h of reperfusion, the infarcted area of heart was measured by Evans blue/triphenyl tetrazolium staining, and the levels of creatine kinase isoenzymes (CK-MB) in serum were detected by enzyme-linked immunosorbent assay. Results: Nalbuphine had no protective effect against the infarct area compared with the control treatment (NAL, 52.5 ± 5% versus CON, 52.6 ± 4%; * P  < 0.01), and the infarct size-sparing effects of morphine were not affected by nalbuphine (NAL + MOR, 42.6 ± 7% versus MOR, 40.4 ± 3%; P  > 0.05). The nalbuphine group did not show a change the levels of serum CK-MB compared with the control group, and nalbuphine did not affect the levels of serum CK-MB in the MOR group. Conclusions: Nalbuphine does not interfere with the cardioprotective effect of morphine in vivo. Therefore, nalbuphine could be safely used or combined with morphine in patients with acute myocardial infarction. Highlights: Morphine induced cardioprotective effects. Nalbuphine did not interfer the cardioprotective effect of morhine. Nalbuphine could be safely selected or combined with morphine for patients with acute myocardial infraction.